Kidney transplantation and cardiomyopathy: Concepts and controversies in clinical decision‐making. Issue 3 (5th February 2020) - Jha, Ajay Kumar; Lata, Suman
Abstract: Increasing comorbidities and an aging population have led to a tremendous increase in the burden of both kidney and cardiac dysfunction. Concomitant cardiomyopathy exposes the patients with kidney disease to further physiological, hemodynamic, and pathologic alterations. Kidney transplantation imposes lesser anesthetic and surgical complexities compared to another solid organ transplant. The surgical decision‐making remains an unsettled issue in these conditions. The surgical choices, techniques, and sequences in kidney transplant and cardiac surgery depend on the pathophysiological perturbations and perioperative outcomes. The absence of randomized controlled trials eludes us from suggesting definite management protocol in patients with end‐stage kidney disease with cardiomyopathy. Nevertheless, in this review, we extracted data from published literature to understand the pathophysiologic interactions between end‐stage renal diseases with cardiomyopathy and also proposed the management algorithm in this challenging scenario. The proposed management algorithm would ensure consensus across all stakeholders involved in decision‐making. Our simplistic evidence‐based approach would augur future randomized trials and would further ensure refinement in our management approach after the emergence of more definitive evidence.